2018
DOI: 10.1097/bsd.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Augmentation is Superior to Nonoperative Care at Reducing Lower Back Pain for Symptomatic Osteoporotic Compression Fractures

Abstract: VA is superior to nonoperative care in reducing lower back pain for osteoporotic VCFs with correlating signs and symptoms. VA had no benefit over nonoperative care for chronic VCFs that lacked clinical correlation. Lower back pain has many etiologies and patients should be clinically assessed before recommending VA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It has been reported that the incidence of non-union in conservative treatment of OVCFs generally ranges from 10-20% [1,4]. In this study, the non-union rate in the low-score group was 2.1%, whereas in the highscore group, it was 67.3%.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It has been reported that the incidence of non-union in conservative treatment of OVCFs generally ranges from 10-20% [1,4]. In this study, the non-union rate in the low-score group was 2.1%, whereas in the highscore group, it was 67.3%.…”
Section: Discussionmentioning
confidence: 49%
“…However, conservative treatment may require a longer rehabilitation process, especially for severe fractures, which may take more time to pain relief and functional recovery. Therefore, some scholars advocate for active surgical treatment [4].…”
mentioning
confidence: 99%
“…OVCF is a common complication in patients with osteoporosis, compared with the conservative treatment of only using drugs and braces, surgical treatment can reduce pain and improve the ability of movement, if the patients do not undergo surgical treatment in time, the vertebral body may continue to collapse, the activity ability of the patient will be weakened, the pain can not be relieved, which result in a low quality of life (14). VA is the main surgical method for OVCFs, and is characterized by reduced trauma, less bleeding, rapid postoperative recovery, and high safety (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is substantial clinical evidence on the safety and effectiveness of both VP and BK for osteoporotic vertebral fractures (OVF) providing greater pain relief and functional recovery than CM [22][23][24][25][26] the costeffectiveness of these procedures is less well known. We previously conducted an up-to-date systematic review of peer-reviewed studies evaluating cost-effectiveness of these procedures for OVFs.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%